Biomarkers in premature calves with and without respiratory distress syndrome. (5th July 2021) - Ider, Merve; Naseri, Amir; Ok, Mahmut; Uney, Kamil; Erturk, Alper; Durgut, Murat K.; Parlak, Tugba M.; Ismailoglu, Nimet; Kapar, Muhammed M.
Abstract: Background: Approaches to the evaluation of pulmonary arterial hypertension (PAH) in premature calves by using lung‐specific epithelial and endothelial biomarkers are needed. Objective: To investigate the evaluation of PAH in premature calves with and without respiratory distress syndrome (RDS) by using lung‐specific epithelial and endothelial biomarkers and determine the prognostic value of these markers in premature calves. Animals: Fifty premature calves with RDS, 20 non‐RDS premature calves, and 10 healthy term calves. Methods: Hypoxia, hypercapnia, and tachypnea were considered criteria for RDS. Arterial blood gases (PaO2, PaCO2, oxygen saturation [SO2 ], base excess [BE], and serum lactate concentration) were measured to assess hypoxia. Serum concentrations of lung‐specific growth differentiation factor‐15 (GDF‐15), asymmetric dimethylarginine (ADMA), endothelin‐1 (ET‐1), vascular endothelial growth factor (VEGF), and surfactant protein D (SP‐D) were measured to assess PAH. Results: Arterial blood pH, PaO2, SO2, and BE of premature calves with RDS were significantly lower and PaCO2 and lactate concentrations higher compared to non‐RDS premature and healthy calves. The ADMA and SP‐D concentrations of premature calves with RDS were lower and serum ET‐1 concentrations higher than those of non‐RDS premature and healthy calves. No statistical differences for GDF‐15 and VEGF were found among groups. Conclusions and Clinical Importance: Significant increases in serum ET‐1 concentrations and decreases in ADMA and SP‐D concentrations highlight the utility of these markers in the diagnosis of PAH in premature calves with RDS. Also, we found that ET‐1 was a reliable diagnostic and prognostic biomarker for PAH and predicting mortality in premature calves.